2018
DOI: 10.14393/bj-v34n6a2018-39587
|View full text |Cite
|
Sign up to set email alerts
|

Protein, lipid and isoflavone contents of food-type soybean lines at two sowing dates

Abstract: Few works have reported the relationship among genotype, temperature, rainfall and the chemical compounds of soybean. Therefore, the aim of this study was to investigate the interaction effect between soybean food-type inbred lines sowed in two different dates and the contents of protein, oil and isoflavones. Eight lines with null lipoxygenase seeds classified as food-type soybean were sowed in October 7 (early sowing) and October 29 (late sowing) at 2013/2014 crop year. The oil, protein and isoflavones conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Magnesium showed significance only for genotype, whereas total phenolic compounds and Cu were not influenced by the studied sources of variation (Table 1). In many studies, grain yield, weight and composition were influenced by genetic and/or environmental factors (Freiria et al, 2016;2018a;2018b) and the interaction between those factors resulted in differences in the performance of each genotype according to climatic conditions such as temperature, precipitation and photoperiod as well as factors related to type of soil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium showed significance only for genotype, whereas total phenolic compounds and Cu were not influenced by the studied sources of variation (Table 1). In many studies, grain yield, weight and composition were influenced by genetic and/or environmental factors (Freiria et al, 2016;2018a;2018b) and the interaction between those factors resulted in differences in the performance of each genotype according to climatic conditions such as temperature, precipitation and photoperiod as well as factors related to type of soil.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature is also the climatic variable most highly correlated with the protein percentage in soybean grains, especially during the grain-fill period. Freiria et al (2016;2018b) found higher protein percentages in higher temperature conditions when these were accompanied by lower precipitation rates.…”
Section: /9mentioning
confidence: 92%
See 1 more Smart Citation